Studies on Recycled Polyester - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Allen, Vincent; Schubert, Dirk W. (Textile Science and Clothing Technology, 2019)
In this chapter, poly(ethylene terephthalate) (PET) melt-spun fibres from five different PET materials were fabricated by a capillary rheometer, which was equipped with an air aspirator for aerodynamic stretching. Two recycled PET of coloured rPET-A and clear rPET-B from waste PET bottle flakes were used, and three virgin PET with different grades of the bottle-grade vPET-2, fibre-grade vPET-1 and fibre-grade vPET-3 were chosen as reference benchmark. During the extrusion process, two processing temperatures of 270 and 280 °C in the capillary rheometer were applied, combined with six different take-up pressures from 0.5 to 3.0 bar for fibre stretching during the spinning process. An empirical equation was given, to predict the water content of PET materials under the specific drying temperature and drying time. Afterwards, the characteristics of the raw materials and drawn PET fibres were discussed comprehensively from the perspective of thermal behaviour, molar mass characteristic, rheological properties, surface morphology, diameter, tenacity and elongation at break. rPET-B and vPET-1 materials yielded optimal spinnability and demonstrated to be the most suitable materials to fabricate fibres with a desirable tenacity, an outstanding elongation at break and an excellent fibre fineness. Crystallinity and orientation of fibres from these two materials were explored to give a potential explanation for the higher tenacity. Furthermore, performance-reliability plots were applied, and a semi-empirical equation was suggested for the first time relating the tenacity and elongation at break of fibres. This study proves the possibility to produce PET fibres from bottle-grade recycled co-polymer PET material, which have similar properties as fibres produced from fibre-grade virgin homo-polymer PET. All the specific information of the five investigated PET materials, especially rPET-B and vPET-1, can provide guidance for melt spinning process in the futur
Keywords: Recycled PET Virgin PET Melt spinning Thermal behaviour Viscosity Surface morphology Mechanical property Semi-empirical equation